Pembelajaran Apresiasi Sastra Melalui Majalah Dinding - Abdul Halim; Nisrina Najla Rifa; Eling Arliyan (Jurnal Guru Indonesia, 2022)
AbstractLiterature is one of the scientific fields that lack more attention, especially in learning literature and appreciating literary works in schools. Appreciation of literature in learning literature in schools still has various problems, including the implementation of literature or its application in learning Indonesian which is still lacking. This study aims to determine the extent to which students at the senior high school level appreciate literature by using wall magazines as media. This research uses a descriptive qualitative method. The data source was obtained from the results of observations made by researchers at the senior high school level. Data collection techniques were obtained from the results of questionnaires distributed to high school students who were then recorded by researchers using the document, reading, and note-taking techniques. Checking the validity of this study uses the source triangulation technique, namely by seeking information. Researchers observe by utilizing the use of existing sources, methods, and theories. The results of the study show that the use of wall magazines (wall magazines) at the high school level to appreciate literary works is still very popular among high school students. AbstrakSastra yang menjadi salah satu bidang keilmuan yang kurang memiliki perhatian lebih khususnya pada pembelajaran sastra dan apresiasi karya sastra di sekolah. Apresiasi sastra dalam pembelajaran sastra di sekolah masih memiliki berbagai permasalahan, diantaranya implementasi sastra atau penerapan dalam pembelajaran bahasa Indonesia yang masih kurang. Penelitian ini bertujuan untuk mengetahui sejauh mana siswa pada jenjang Sekolah Menengah Atas dalam mengapresiasi sastra dengan menggunakan media majalah dinding. Penelitian ini menggunakan metode kualitatif deskriptif. Sumber data diperoleh dari hasil observasi yang dilakukan peneliti pada sekolah jenjang Sekolah Menengah Atas. Teknik pengumpulan data diperoleh dari hasil kuesioner yang disebarkan kepada siswa Sekolah Menengah Atas yang kemudian didata oleh peneliti dengan teknik dokumen, membaca, dan mencatat. Pengecekan keabsahan dalam penelitian ini  menggunakan teknik trigulasi sumber yaitu dengan mencari informasi. Peneliti mengamati dengan cara memanfaatkan penggunaan sumber, metode, dan teori yang sudah ada. Hasil penelitian menunjukkan bahwa Penggunaan media mading (majalah dinding) pada jenjang SMA dalam upaya mengapresiasi karya sastra masih sangat pupuler di kalangan siswa-siswi SMA.